Equity crowdfunding platforms and sustainable impacts: encountering investors and technological initiatives for tackling social and environmental challenges - YÁÑEZ VALDÉS, CLAUDIA FERNANDA; GUERRERO CANO, MARIBEL (My University, 2023)
PurposeInnovative initiatives focusing on social and environmental impact often need help to secure traditional financial resources for their launch. Equity crowdfunding platforms (ECF) provide a potential funding source for these initiatives, particularly for technological inventors. This research paper aims to theorize how ECF campaigns attract investors to invest in technological initiatives with social and environmental value proposition impacts.Design/methodology/approachUsing an inductive qualitative approach, the authors have gained insights, from 35 sustainable technological projects sponsored by a Chilean equity-crowdfunding platform, regarding the business model's transformation to achieve sustainable social and environmental impacts.FindingsFindings show that disruptive technologies and sustainable aims are pivotal factors in successfully attracting investors to support sustainable technological initiatives through ECF platforms or campaigns. These factors led investors to actively engage with these projects and contribute to the value-creation process by transforming business models with social and environmental impacts and utilizing sustainable technology to enhance efficiency and optimize available resources.Research limitations/implicationsDue to the nature of this research, researchers must test the proposed conceptual framework using longitudinal quantitative data from multiple ECF platforms, technological solutions and investors worldwide in future research to enhance the comprehension of this phenomenon.Practical implicationsThe findings highlight the significant contribution of ECF platforms and technological portfolios toward creating sustainable impacts. It is a good signal for investors interested in investing in technological initiatives and addressing social and environmental challenges.Social implicationsThe contribution of disruptive technological projects from ECF platforms and ECF investors to tackle social and environmental challenges.Originality/valueThis research theorizes how ECF platforms tackle social challenges by encouraging investors to invest and participate with entrepreneurs in the co-creation process of sustainable technological solutions.
Keywords: crowdfunding; environmental innovation; equity-crowdfunding; investors; social innovation; sustainable impacts; technological projects